(untitled) (Kinesiology, 2017)
There are many determinants of sports motivation such as athletes’ personal characteristics, coaches, peers, parents and the other environmental factors. In this research, the aim was to analyse whether there was a relationship between perceived parent-initiated motivational climate and self-determined motivation of karate athletes. Karate athletes (N=325) participated in the research and completed the adolescent version of the Sport Motivation Scale and Parent-Initiated Motivational Climate Questionnaire. Multiple regression analyses showed that the athletes’ self-determined motivation significantly correlated with learning and enjoyment climate, worry-conducive climate and success-without-effort climate perceived both in father and mother. Besides, regression analysis showed that perceived family climate significantly contributed to selfdetermined motivation. Linear combination of father learning and enjoyment climate (β=.21), father successwithout effort climate (β=-.17), and mother success-without-effort climate (β=-.14) significantly contributed to self-determined motivation (F(3,321)=18.88, R2=.15, p<.001). In conclusion, the results indicated that athletes’ perception of parent-initiated motivational climate was important for their self-determined motivation. The findings were evaluated and some implications for parents were proposed. Key words: autonomous motivation, worry-conducive climate, learning and enjoyment climate